FEATURES OF PARTICIPATION OF RUSSIA IN THE WORLD MARKET OF OIL DURING THE PERIOD FROM 1992 TO 2013 IN THE CONTEXT OF THE FAVORABLE PRICE ENVIRONMENT - A. Rudneva (Вестник университета)
In the article influence of the favorable price environment is analyzed in the world market of oil on production and export of oil in Russia during the pre-sanctions period with use of the retrospective analysis on the basis of the statistical data from 1992 to 2013. The particular emphasis is placed on the stimulating function of the price in the conditions of its growth inducing to speeding up of production and export of power raw materials. The author refers loss of sensitivity to price signals at the present stage to aspect of strategy of repartition of the world market of oil, for preservation of positions on which Russia should be overcome.